Learning Organization Practices in The Development of Public Service Innovation (Case Study of E-Id Card and Birth Certificate Services at The Bantul Regency Population and Civil Registration Office) - Purnomo Purnomo; Puguh Prasetya Utomo; Dewi Haryani Susilastuti (Return : Study of Management, Economic and Bussines, 2025)
This research reveals empirical practices of learning organizations in developing service innovations through a case study approach. The study examines learning organization practices implemented by the Population and Civil Registration Office of Bantul Regency, particularly in developing Identity Card (ID) and Birth Certificate services. The Bantul Population and Civil Registration Office prioritizes service convenience and speed aspects in developing ID and Birth Certificate service innovations. The development of ID service innovations at the Bantul Population Office was significantly influenced by substantial public demands for services, while Birth Certificate services did not generate such large demands from the community. The crisis (COVID-19 pandemic) that occurred from 2020 to 2022 impacted ID and Birth Certificate services, making the Population Office more intensively innovate in developing these services. After the crisis ended, innovations developed during the crisis were maintained and continued, with only the application usage aspect in ID services being further developed. The development of service innovations for both IDs and Birth Certificates in normal and crisis situations at the Bantul Population Office demonstrates the role of learning organizational practices. The organization's ability to understand each population service regulation impacts organizational flexibility in providing services, strengthening collaborative spirit both among employees and between teams/groups. Work designed for mutual learning through organizational support provides discussion spaces for employees and opportunities to gain knowledge outside the organizational environment. Improvements in ID and Birth Certificate services are also significantly influenced by employee empowerment through involvement of all employees in decision-making processes.